Septris: A Novel, Mobile, Online, Simulation Game That Improves Sepsis Recognition and Management. (February 2015) - Evans, Kambria H.; Daines, William; Tsui, Jamie; Strehlow, Matthew; Maggio, Paul; Shieh, Lisa
Abstract : Problem: Annually affecting over 18 million people worldwide, sepsis is common, deadly, and costly. Despite significant effort by the Surviving Sepsis Campaign and other initiatives, sepsis remains underrecognized and undertreated. Approach: Research indicates that educating providers may improve sepsis diagnosis and treatment; thus, the Stanford School of Medicine has developed a mobile-accessible, case-based, online game entitled Septris (http://med.stanford.edu/septris/ ). Septris, launched online worldwide in December 2011, takes an innovative approach to teaching early sepsis identification and evidence-based management. The free gaming platform leverages the massive expansion over the past decade of smartphones and the popularity of noneducational gaming. The authors sought to assess the game's dissemination and its impact on learners' sepsis-related knowledge, skills, and attitudes. In 2012, the authors trained Stanford pregraduate (clerkship) and postgraduate (resident) medical learners (n = 156) in sepsis diagnosis and evidence-based practices via 20 minutes of self-directed game play with Septris. The authors administered pre- and posttests. Outcomes: By October 2014, Septris garnered over 61, 000 visits worldwide. After playing Septris, both pre- and postgraduate groups improved their knowledge on written testing in recognizing and managing sepsis ( P < .001). Retrospective self-reporting on their ability to identify and manage sepsis also improved ( P < .001). Over 85% of learners reported that they would or would maybe recommend Septris. Next Steps: Future evaluation of Septris should assess its effectiveness among different providers, resource settings, and cultures; generate information about how different learners make clinical decisions; and evaluate the correlation of game scores with sepsis knowledge.